2018
DOI: 10.3329/bjvm.v15i2.35521
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Anthropo-Clinical Study on Antimicrobials Prescription Pattern in Goat Patients at Chittagong, Bangladesh

Abstract: In the last three decades use of antibiotics in livestock sector has grown tremendously. The uses of these antibiotics have profound impacts on animal health, farmer income and public health. From April, 2016 to March, 2017, a hospital based retrospective study was conducted using clinical record sheet of goat patients (N=1405) at Teaching Veterinary Hospital (TVH) of Chittagong Veterinary and Animal Sciences University (CVASU), Bangladesh; to assess the groups of antimicrobials used, perception of goat owners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Farmers' wisdom about the use of antibiotics is another important determinant to provoke the problem of antibiotic resistance [60]. A study showed that most farmers have no clear idea about AMR and the withdrawal period of antibiotics [61]. Resistance to antibiotics includes -first, transfer of AMR pathogens through the food chain, and transfer of AMR genes from animal enteric flora to human pathogens.…”
Section: Amrmentioning
confidence: 99%
“…Farmers' wisdom about the use of antibiotics is another important determinant to provoke the problem of antibiotic resistance [60]. A study showed that most farmers have no clear idea about AMR and the withdrawal period of antibiotics [61]. Resistance to antibiotics includes -first, transfer of AMR pathogens through the food chain, and transfer of AMR genes from animal enteric flora to human pathogens.…”
Section: Amrmentioning
confidence: 99%
“…This has resulted in the presence of pathogenic bacteria resistant to commonly used antimicrobials in water resources and salad vegetables which are significant from a public health perspective [53][54][55][56][57]. The prevalence of Salmonella species was found to vary between 60% to 78% in different street foods in Chittagong while multidrug resistant Salmonella was found in each of the food items tested [58]. Besides, antimicrobials were found to be used routinely to increase food animal production, resulting in the spread of antibiotic resistant organisms from farms to environment to community [53].…”
Section: Situation In Food Animals Fisheries and Environment Includmentioning
confidence: 99%
“…Besides, antimicrobials were found to be used routinely to increase food animal production, resulting in the spread of antibiotic resistant organisms from farms to environment to community [53]. Around 24% of goat farmers mentioned that they were familiar with the term antibiotic but none of them had any idea about antimicrobial resistance nor withdrawal period [58]. The hospitals of Dhaka city are also contributing to the process by discharging untreated medical wastes in the water, resulting in the presence of high-levels of resistant E. coli in the water [53].…”
Section: Situation In Food Animals Fisheries and Environment Includmentioning
confidence: 99%
“…In livestock, antibiotics are mainly used to treat diseases. Two hospital-based studies reported that antimicrobials were prescribed to treat 56–66% of sick animals [ 58 , 59 ]. The most commonly prescribed antibiotics were streptomycin–penicillin (31%) followed by sulfadimidine (14%), amoxicillin (11%), gentamicin–sulfadiazine–trimethoprim combination (9%), and tylosin (1%) [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two hospital-based studies reported that antimicrobials were prescribed to treat 56–66% of sick animals [ 58 , 59 ]. The most commonly prescribed antibiotics were streptomycin–penicillin (31%) followed by sulfadimidine (14%), amoxicillin (11%), gentamicin–sulfadiazine–trimethoprim combination (9%), and tylosin (1%) [ 58 ]. Shiga toxin-producing E. coli (STEC) and enterotoxigenic E. coli (ETEC) showed multidrug-resistant against erythromycin, trimethoprim–sulfamethoxazole, azithromycin, cephalothin, ciprofloxacin, and nalidixic acid [ 60 ].…”
Section: Resultsmentioning
confidence: 99%